Diseño de un plan estratégico de marketing para la microempresa Variedades TV, ubicada en el centro histórico de la ciudad de Quito D.M. - Rumiguano Aleman, Angel Ramiro (2010)
The present work aims to design a strategic marketing plan for micro "Variety TV", located in the historic center of Quito DM, aimed at meeting the needs of consumers through having a plan will serve as a basis for the implementation of actions set, enrumbadas towards achieving its objectives, with proposed strategies and the corresponding sequence of activities in monitoring them.